Control software for droplet-based microfluidics - Nguyen, Nam Trung. (2010)
This project aims at the integration of peripheral hardware into a single system, which is controllable from a PC. We have successfully used MATLAB purchased from the grant to control existing peripheral devices such as syringe pump, data acquisition cards, and digital camera. As demonstrations, programs for automatic data acquisition of microfluidic devices were written and tested. In the first MATLAB program, pressure versus flow data of passive microfluidic devices was collected by controlling a syringe pump and the data acquisition card. In the second MATLAB program, the control of the inverted fluorescent microscope is demonstrated. The platform is capable of controlling the droplet-based microfluidic platform resulting from the current SERC project.